MELON HOMEPAGE MAKING HYBRID USING MACROMEDIA DREAMWEAVER 3.0 - Muhammad Iqbal; Cut Asiana Gemawaty. Skom. MMSi Cut Asiana Gemawaty. Skom. MMSi (Jurnal Sistem Informasi, 2002)
From the description on this scientific writing, the writer can take the conclusion thatcreating a homepage is not too difficult, even for beginners because conveniencefacilities provided by Macromedia Dreamweaver 3.0 and Dreamweaver softwaresupport from the tutorial itself.Must be considered in making a web site is in the provision of images, graphics, text,and others. Giving a lot of pictures on the web was going to make the website lookmore attractive, but for Internet users that have a low-class computers will requiresubstantial memory and this will slow down a website link.